1991
DOI: 10.1159/000186643
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgA Class Anti-IgA Antibody in IgA Nephropathy

Abstract: IgA class anti-IgA antibody was sought by an immunoabsorbent technique in sera from patients with IgA nephropathy (IgA-N, n = 62), other forms of primary glomerulonephritis (PGN, n = 41), seropositive rheumatoid arthritis (RF-positive, n = 18) and normal controls (c, n = 50). IgA-N (31%) and RF-positive (56%) patients showed a significant increase in IgA anti-IgA antibody levels. The subclass of IgA anti-IgA antibody was predominantly IgAl in both IgA-N and RF-positive patients. Size analysis revealed the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This would readily explain the weak affinity of binding between Fab and Fc in rheumatoid factors, and the mon ovalency of their interaction with IgG [23] and their selective cross-reactivity with IgG from other species [23,24]. We previously reported a significant increase of serum IgA having an affinity to human IgA in patients with IgAN and with seropositive RA [25]. The IgA was speculated to be one of the rheumatoid factors because of the positive results in seropositive RA patients and the existence of IgA rheumatoid factor in IgAN patients [26,27], This hypothesis that the formation of macromolecule IgA is not due to an immunological mechanism would resolve the question put forth by Shibata [28] as to why the clinical course of IgAN is continuous and slowly pro gressive.…”
Section: Discussionmentioning
confidence: 99%
“…This would readily explain the weak affinity of binding between Fab and Fc in rheumatoid factors, and the mon ovalency of their interaction with IgG [23] and their selective cross-reactivity with IgG from other species [23,24]. We previously reported a significant increase of serum IgA having an affinity to human IgA in patients with IgAN and with seropositive RA [25]. The IgA was speculated to be one of the rheumatoid factors because of the positive results in seropositive RA patients and the existence of IgA rheumatoid factor in IgAN patients [26,27], This hypothesis that the formation of macromolecule IgA is not due to an immunological mechanism would resolve the question put forth by Shibata [28] as to why the clinical course of IgAN is continuous and slowly pro gressive.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that IgAassociated molecules including dimeric IgA (11s) itself must contribute to the increased IgA 1 in these fractions during adolescence, since an increased production of dimeric IgA in the bone marrow [24] or an increased ratio of dimeric IgA 1 to polymeric IgA 1 in serum [25] has been demonstrated in patients with IgA nephropathy. Sancho et al [17] showed that some monomeric as well as polymeric IgA was present as immune complexes in the SDGU fractions with large sedimentation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…From my previous paper on IgA-IgA binding [9] and as described in the section on CIC theory, I suspected that the incomplete carbohydrate chains in IgA1 molecules may induce self-aggregation of IgA molecules in IgAN patients. The stability of IgA1 molecules in serum samples was assessed by observing the increase in turbidity of the sample, which reflects an increase in aggregated IgA1, upon heating the sample to 63掳C [31].…”
Section: Self-aggregation Of Aberrant Iga1mentioning
confidence: 99%
“…However, the theory was not consistent with the fact that the staining intensity of IgG deposition in the mesangial area was much less than that of IgA deposition in IgAN patients. On the basis of these published reports, I started to analyze the IgA that tended to bind to IgA, found that its level was increased in IgAN patients, and reported it as IgA-type anti-IgA-antibody [9]. During the course of the experiment, the question of ''Is this IgA-IgA binding really due to an immunological interaction?''…”
mentioning
confidence: 99%